A novel approach for failure mode and effect analysis in propeller shaft manufacturing industry using fuzzy analytic hierarchy process and GRA VIKOR. (3rd May 2019) - Sakthivel, G.; Ikua, Bernard W.
The present study develops the evaluation model based on FMEA and AHP integrated with GRA VIKOR under fuzzy environment to evaluate the greatest risk for processes in the production of dust cap assembly in the propeller shaft manufacturing industry. Three risk factors S, O, D and their weights are treated as fuzzy triangular linguistic variables to eliminate the risk for production. FAHP is used to compute the weights of S, O, D whereas GRA VIKOR is used to obtain the final ranking of a risk alternative. Here, the risk factors and their weights are treated as fuzzy triangular linguistic variables for eliminating the risk of subjective quantification and similarity of risk priority number (RPN). Among the various failures, drawing dimension failure and blanking of blank failure are obtained as the most serious failure modes using fuzzy GRA VIKOR.